2023
DOI: 10.3390/epidemiologia4020015
|View full text |Cite
|
Sign up to set email alerts
|

Computer Skills and Electronic Health Records (EHRs) in a State Tertiary Hospital in Southwest Nigeria

Abstract: Adopting change is something that is often resisted, as is often the case in the adoption of electronic health records (EHRs) in healthcare organizations. Embracing this will require computer knowledge to handle the system for the management of patients and their care. This study aims to determine the computer skills required for the uptake of electronic health records (EHR) by healthcare workers in an annex of the state teaching hospital, Okela Health Centre (OHC) Ado-Ekiti. The study uses a cross-sectional r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…However, there are 21.7% health workers who do not access or use MS Words to support their work at home and in the workplace. The result is corresponding to the previous research by another scientist conducted that health workers in some parts of the hospital in Africa's majority of respondents explained that they used Microsoft Word to be very efficient with a total percentage of 63.4% [15]. Health workers working in hospital, community health center, central service the Ministry of Health and university throughout the territory of Timor-Leste is obliged to understand the use of Microsoft Word.…”
Section: Digital Technology Utilization Experiencessupporting
confidence: 80%
See 2 more Smart Citations
“…However, there are 21.7% health workers who do not access or use MS Words to support their work at home and in the workplace. The result is corresponding to the previous research by another scientist conducted that health workers in some parts of the hospital in Africa's majority of respondents explained that they used Microsoft Word to be very efficient with a total percentage of 63.4% [15]. Health workers working in hospital, community health center, central service the Ministry of Health and university throughout the territory of Timor-Leste is obliged to understand the use of Microsoft Word.…”
Section: Digital Technology Utilization Experiencessupporting
confidence: 80%
“…Email and WhatsApp's use Based on the above result also indicated that majority of health workers in Timor-Leste was have ability and opportunity to access use e-mail and WhatsApp's on supporting their daily work is 89.2% and 91,7%. This result was according with the other several result study was mentioned that the ability in e-mail and WhatsApp use was efficiency is 76.4% and 73.3% [15]. Other study also was reported that in the South East Asia Region (SEARO) as only 5 countries was adapted the telemedicine guideline to support health workers during conducting the health care to the population, that is India, Bangladesh, Thailand, Indonesia and Nepal only [16].…”
Section: Digital Technology Utilization Experiencessupporting
confidence: 63%
See 1 more Smart Citation
“…The authors showed that over half of the comments pointed to problems with the system itself (e.g., poor system usability, nonintegrated systems, poor interoperability, a lack of standards, and limited functionality/missing components), followed by problems with user tasks (e.g., the failure of systems to meet nursing clinical needs and non-nursing-specific systems), and problems with their working conditions (e.g., the low prevalence of EHRs, and a lack of user training). In addition, in a study conducted in a State Tertiary Hospital in Southwest Nigeria to investigate healthcare workers' computer skills during the uptake of EHRs, researchers found that the majority of the participants did not have sufficient skills in Microsoft Excel and Microsoft Access [41]. Other barriers were reported by a systematic review study, such as inappropriate resources, training, and technical and educational support, as well as poor skills and literacy of healthcare providers [15].…”
Section: Discussionmentioning
confidence: 99%
“…As shown in one study, most nurses in Lesotho do not have adequate computer skills, which is strongly correlated with the length of time that has passed since they last obtained a qualification and with a lack of exposure to computers [44]. Nurses' willingness to adopt computerization is indicative of their understanding of the merits of using technology in their profession [41]. This willingness of nurses to adopt EHR means that they are aware of the positive effects that innovations and informatics can have on high-quality nursing practice and how this impacts the patients' health [39].…”
Section: Discussionmentioning
confidence: 99%